Pengembangan Bag Valve Mask (BVM) Otomatis - Rofi i, Mohamad; Sofie, Mohamad; Olla, Patrisius Kusi (Universitas Semarang, 2022)
Ventilators are one of the medical devices that are needed as a breathing apparatus for COVID-19 patients who have respiratory problems. One of the low-cost ventilators currently being developed by several domestic institutions is the ambu bag-based ventilator. The point is an air bag (bag) that is pressed by two carefully controlled automatic clamps, so that it can reach all, while taking into account portability, aesthetics and ease of manufacture. Therefore, the Bag Valve Mask (BVM) or ambu bag is an emergency option to replace the function of the ventilator. This study aims to make an ambu bag that can be applied as a portable mechanical ventilator. Thus, the ambu bag which was originally used manually can be used automatically like a ventilator machine in general. In determining the type of mechanical arm pressure, several parameters such as minute volume, respiratory rate, and tidal volume are used. As recommended by the American Heart Association (AHA) that the tolerance limit for the RR value is +/-10 BPM, it can be said that the automatic BVM as a result of this study can be used with or without a reservoir as needed or with the addition of oxygen